Supporting east Asian students enrolled at a South African university - Xie, Tao (University of the Free State, 2019)
Over the previous 30 years, most East Asian (South Korea, China, Japan) countries have achieved remarkable economic success, and are entering the global economic market. Therefore, more and more East Asian parents support their children to study in other countries. Chinese parents, for example, may consider that studying overseas inter alia would enhance their children's competitiveness in terms of learning other languages, especially English and understand different cultures, getting a good quality of education, learning from other countries’ different sets of values. They thus consider studying overseas as a long-term investment towards global citizenship. Due to different language, culture, and learning styles between the East Asian and English-speaking countries, these students often find it difficult to adapt to the new environment. As an East Asian student myself, I had found it difficult to adapt to the circumstances in South Africa. As I could find no reference in literature to the problem in the context of South Africa, the aim of my dissertation was to explore and describe the challenges of East Asian students studying at one South African English-medium university towards improving the support provided by higher education institutions. Based on my literature review I gathered that East Asian students studying abroad often find challenges with academic and social practices. The literature also highlighted difficulties in terms of transport and accommodation. The level of support varies at different institutions, and in different parts of the world. Based on my literature review, I developed some interview questions which I posed to six East Asian participants and seven staff members at the University of the Free State. I transcribed the data, and sorted similar themes based on what the literature and data indicated as relevant. My study showed that East Asian students experience barriers with regard to language and the academic practices. In terms of language, the students shared that it was difficult to understand English, and in particular also to follow the different accents. Adjusting to continuous assessments, with diverse assessment tasks was also difficult, as it is quite different from the systems used in their own countries.The interviews with the staff members revealed that many units exist to assist the students, albeit not specifically for East Asian students. Services include support for international students in terms of administrative issues such as study permits, registration and so forth. There are units that assist students with academic writing, studying methods and many more. For me, the most significant observation was that while the East Asian students were struggling, the university seemed to have numerous support structures in place that could help them to overcome these challenges. However, the students seemed to be unaware of the services that they could make use of. It became clear that it is vitally important that universities find a way to continuously make English as a Foreign Language (EFL) students aware of the services that could assist them.
Dissertation (M.Ed. (Higher Education Studies))--University of the Free State, 2019
Keywords: International students; Student support; Foreign students; East Asian; South African university